Estudio urodinámico del tracto urinario superior. - Crespi Martínez, F.; Fuentes Márquez, I.; Moreno Casado, Mª J.; Resel, Luis; Silmi Moyano, A. (Clínicas Urológicas de la Complutense, 2002)
Sin resumen